(untitled) (Philology, 2026)
There are proverbs and phraseological units that relate to the language of only one nation, as well as proverbs and phraseological units borrowed from other languages, both orally and in writing. Such borrowings occurred and are currently occurring in connection with the expansion of cultural exchange, the development of trade relations between people, particularly between Turkmen and Iranian people, living in the neighborhood. Proverbs of this kind, along with those originally belonging to one specific nation, occupy a strong place in the lexical composition of the language that inherited them. Over time, their non-local origin gradually ceases to be felt. In numerous works of poets, writers, works of thinkers of both past centuries and our contemporaries, one can see their quite active use of proverbs and sayings, phraseological set expressions and catchwords. One of the Turkmen poets, who widely used proverbs, phraseological units and wise sayings in his works, is Magtymguly Pyragy. In the course of a comparative analysis of proverbs and phraseological units found in the works of Magtymguly, the following types of phrases were identified, characterized by varying degrees of similarity with Persian phraseological units and proverbs: complete and incomplete, as well as partial. Most of the phraseological units used in Magtymguly’s poems are extremely common and relevant today. It should be noted that the study of proverbs and phraseological units gives us a lot of valuable information about the culture, spiritual values, moral guidelines, traditions and customs, and social priorities of different nations. By comparing proverbs and phraseological expressions of the Turkmen and Persian languages, one can find similarities and differences between the perception of the world of one or another nation, as well as identify features characteristic only of a certain nation.